UPAYA GURU MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN KESEJAHTERAAN KELUARGA DENGAN METODE PRAKTIK DI SEKOLAH MENENGAH PERTAMA NEGERI 5 PANGGANG GUNUNGKIDUL YOGYAKARTA - Esti Supraptiningsih; Sri Wahyu Andayani (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2015)
The purpose of the research is to investigate(1) the use of practical method can improve the quality of learning and (2) the use of practical method can increase the activity of students of SMPN 5 PanggangÂ Gunungkidul Yogyakarta in following learning PKK.The type of the research is classroom action research. The subjects of the research grade IX students. There were 20 students. The object of the research is the teaching and learning process. The instruments of the research are observation sheet and test. The data were collected though descriptive quantitative technigue. The finding of the research shows that partical method can improve the quality of learning practice of PKK in SMPN 5 Panggang Gunungkidul Yogyakarta. The improvement of the PKK learning process can be seen from the result of the test in each cycle. In cycle I, there was on improvement of the average from 53,25 in the pre-liminary study into 58,25 with 10% improvement of classical mastery. In cycle II, the average was 69,25 with classical mastery increased 35% above the researchers target. In conclusion, practical method can be applied to improve the quality of PKK learning process.Â